1996
DOI: 10.1111/j.1399-0004.1996.tb02376.x
|View full text |Cite
|
Sign up to set email alerts
|

Late juvenile metachromatic leukodystrophy (MLD) in three patients with a similar clinical course and identical mutation on one allele

Abstract: Metachromatic leukodystrophy (MLD) is an autosomal, recessively inherited, lysosomal storage disease caused by arylsulfatase A (ASA) activity deficit. Arylsulfatase A initiates the degradation of sulfatide (cerebroside sulfate), which is an essential component of myelin. The main clinical symptoms are caused by progressive demyelination. At least 37 MLD‐related ASA mutations are known to date. I179S (E3P799) is a disease‐related mutation, described for the first time by Fluharty in 1991. This aberration appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Late-onset (adult) MLD is characterized by low residual ASA activity (von Figura et al, 2001). Characteristic symptoms in adult MLD are schizophrenialike behavioral abnormalities [in patients with the I179S mutation (Tylki-Szymanska et al, 1996)] or clumsiness of movement and spastic paresis of arms and legs [in patients with the P426L mutation (Berger et al, 1997)]. In contrast, nerve conduction velocity is sometimes normal, and signs of peripheral neuropathy and demyelination are often absent (Kolodny and Fluharty, 1995).…”
Section: Cortical Hyperexcitability In Asa(؊/؊) Micementioning
confidence: 99%
“…Late-onset (adult) MLD is characterized by low residual ASA activity (von Figura et al, 2001). Characteristic symptoms in adult MLD are schizophrenialike behavioral abnormalities [in patients with the I179S mutation (Tylki-Szymanska et al, 1996)] or clumsiness of movement and spastic paresis of arms and legs [in patients with the P426L mutation (Berger et al, 1997)]. In contrast, nerve conduction velocity is sometimes normal, and signs of peripheral neuropathy and demyelination are often absent (Kolodny and Fluharty, 1995).…”
Section: Cortical Hyperexcitability In Asa(؊/؊) Micementioning
confidence: 99%
“…Among these, two different clinical presentations have been observed: patients with progressive motor or sensory deficits and, on the other hand, cases with mental disturbance. [3][4][5][6][7][8][9][10][11][12] It has been suggested that these differences may originate from different specific mutations. 1,7,12 To explore a possible genotype-phenotype correlation in late-onset MLD on the basis of specific mutations, we studied the molecular and clinical data of 22 patients homozygous for mutation P426L and of 20 patients heterozygous for mutation I179S.…”
mentioning
confidence: 99%
“…The number of mutations found so far in adult MLD patients is quite limited. Beside a common missense mutation, P426L, predominantly found in patients with motor disturbances, another missense mutation, I179S, was found in adult MLD patients (Tylki-Szymanska et al, 1996;Halsall et al, 1999;Baumann et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Whereas Gieselmann et al (1994) showed that most adult motor forms of MLD present with a specific homozygous missense mutation, P426L, Baumann et al (2002) and others (Tylki-Szymanska et al, 1996;Halsall et al, 1999) reported on patients with the psycho-cognitive form, who were heterozygous for a specific mutation, I179S, together with an allele found in infantile cases. Recently, a homozygous patient with a novel mutation, F219V, a woman with progressive psycho-cognitive impairment without clinical or electrophysiological signs of peripheral nerve involvement, has been described (Maracao et al, 2005).…”
Section: Introductionmentioning
confidence: 96%